1952
DOI: 10.1152/ajplegacy.1952.171.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inulin and Creatinine Clearance in the Normal Dog

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

1953
1953
1974
1974

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…During inflation of the cuff the creatinine-inulin clearance ratio averaged 0.89 for the left (control) and 0.88 for the right (experimental) kidney. These creatinine-inulin clearance ratios are slightly lower than has been found previously (12), but, except for two aberrant periods (among approximately 100) yielding ratios of 0.58 and 0.61, there was no tendency for the clearances to diverge during the experimental manipulations. It is therefore concluded that changes in the clearance of either substance reflected similar changes in the rate of glomerular filtration.…”
Section: Resultscontrasting
confidence: 58%
“…During inflation of the cuff the creatinine-inulin clearance ratio averaged 0.89 for the left (control) and 0.88 for the right (experimental) kidney. These creatinine-inulin clearance ratios are slightly lower than has been found previously (12), but, except for two aberrant periods (among approximately 100) yielding ratios of 0.58 and 0.61, there was no tendency for the clearances to diverge during the experimental manipulations. It is therefore concluded that changes in the clearance of either substance reflected similar changes in the rate of glomerular filtration.…”
Section: Resultscontrasting
confidence: 58%
“…Creatinine was determined by the method of Kennedy, Hilton, and Berliner (5) and inulin by the method of Walser, Davidson, and Orloff (6). Urine and plasma osmolality were determined cryoscopically using the instrument developed by Bowman, Trantham, and Caulfield (7).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that urine remained hypotonic to plasma during the administration of either 0. 5 rates of vasopressin administration over the range of solute excretion examined in these studies. 8 The transition in urine concentration from hypertonic to hypotonic observed when 1.5 to 4.0 mU per Kg.…”
Section: Methodsmentioning
confidence: 99%
“…As the operative procedure was begun, the animal was given intravenously within a 5 to 24-minute period 400 Creatinine was determined in diluted urine and protein free filtrates of plasma by the method of Kennedy, Hilton, and Berliner (5). Total CO2 in plasma and urine was determined by the manometric extraction technique of Van Slyke and Neill (6).…”
Section: Methodsmentioning
confidence: 99%